Paradigma Baru Birokrasi Pemerinthan dalam Mewujudkan Tata Kelola Pemerintahan yang Baik - Afrizal, Afrizal (Kemudi, 2016)
Substitution of the new order regime reform era to bring home big enough task for holders of development policy in this country . Government bureaucracy into one part left by the new order of special concern by the government , especially pemerintaha area. The inability of the government to manage the bureaucracy caused by many things one of which is the lack of quality of personnel in providing service to the community . Apparatus still positioning itself not as a public servant but someone who must be served . Therefore, in this paper the author tries to analyze the problems with the approach of a paradigm shift regarding the bureaucratic apparatus of government as part of efforts to resolve the issue of government bureaucracy in order to realize good governance.